What are mycorrhizal traits? - Chaudhary, V Bala; Holland, E Penelope; Charman-Anderson, Suw; Guzman, Aidee; Bell-Dereske, Lukas; Cheeke, Tanya E; Corrales, Adriana; Duchicela, Jessica; Egan, Cameron; Gupta, Manju M; Hannula, S Emilia; Hestrin, Rachel; et al. (Trends in ecology & evolution, 2022)
Traits are inherent properties of organisms, but how are they defined for organismal networks such as mycorrhizal symbioses? Mycorrhizal symbioses are complex and diverse belowground symbioses between plants and fungi that have proved challenging to fit into a unified and coherent trait framework. We propose an inclusive mycorrhizal trait framework that classifies traits as morphological, physiological, and phenological features that have functional implications for the symbiosis. We further classify mycorrhizal traits by location - plant, fungus, or the symbiosis - which highlights new questions in trait-based mycorrhizal ecology designed to charge and challenge the scientific community. This new framework is an opportunity for researchers to interrogate their data to identify novel insights and gaps in our understanding of mycorrhizal symbioses.
Keywords: fungal traits; mycorrhizas; Symbiosis; rostliny; Phenotype; plant traits; Mycorrhizae; symbiosis; mykorhiza; symbióza; fenotyp; Ecology; ekologie; Plants; ecosystem function; community ecology